Perkembangan dan Pelaksanaan Lembaga Wakaf di Negara Sekuler: Studi Kasus Singapura dan Thailand - Dewi, Kemala; S, Syahfawi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the development and implementation of endowment institutions in two secular countries in southeast asia, namely singapore and thailand. Both countries have minority muslim communities that are active in managing endowment assets despite not being in a shariah-based legal system. This study aims to analyze the concept, history, management, as well as the administration system of endowments in each country. Study results show that singapore, through official institutions such as the muslim ugama majlis singapore (muis), has managed to manage endowments professionally, transparently, and modernly. In contrast, thailand still faces challenges in terms of legality, documentation, and efficiency of endowment management because management is still local and traditional in nature. Despite this, endowments in both countries continue to play an important role in supporting the social, religious, and educational activities of muslim communities. This study affirms the importance of institutional support, adaptive regulation, and public participation in endowment management in secular countries.